World Economic Forum sets up Centre for the Fourth Industrial Revolution in Mumbai - Reliance Industries Limited (2022)
World Economic Forum sets up Centre for the Fourth Industrial Revolution in Mumbai – in partnership with Reliance Industries Limited.